2021
DOI: 10.1186/s12929-021-00740-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of COVID-19 B-cell epitopes with phage-displayed peptide library

Abstract: Background Coronavirus disease 19 (COVID-19) first appeared in the city of Wuhan, in the Hubei province of China. Since its emergence, the COVID-19-causing virus, SARS-CoV-2, has been rapidly transmitted around the globe, overwhelming the medical care systems in many countries and leading to more than 3.3 million deaths. Identification of immunological epitopes on the virus would be highly useful for the development of diagnostic tools and vaccines that will be critical to limiting further spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Meanwhile, the S protein plays a significant role in viral fusion and entry into host cells and is composed of S1 RBD at N-terminus and S2 subunits at C-terminus [ 165 ]. Previous reports indicated that both NP and S protein are immunogenic, as Abs against NP and the RBD of S protein as well as their B cell epitopes were readily detected upon early seroconversion in COVID-19 patients [ 166 169 ]. ELISAs using NP and RBD of S protein show high specificity and no cross-reactivity with non-CoV, HCoV, MERS-CoV, or SARS-CoV [ 170 , 171 ].…”
Section: Antibody-based Sars-cov-2 Detectionmentioning
confidence: 99%
“…Meanwhile, the S protein plays a significant role in viral fusion and entry into host cells and is composed of S1 RBD at N-terminus and S2 subunits at C-terminus [ 165 ]. Previous reports indicated that both NP and S protein are immunogenic, as Abs against NP and the RBD of S protein as well as their B cell epitopes were readily detected upon early seroconversion in COVID-19 patients [ 166 169 ]. ELISAs using NP and RBD of S protein show high specificity and no cross-reactivity with non-CoV, HCoV, MERS-CoV, or SARS-CoV [ 170 , 171 ].…”
Section: Antibody-based Sars-cov-2 Detectionmentioning
confidence: 99%
“…Our novel vaccine strategy, i.e., taking advantage of both the adjuvant and the tetanus toxoid in a tetanus vaccine, is different from other COVID-19 peptide vaccine strategies published in the literature, i.e., focusing on B-cell and T-cell epitope identification and adjuvant development [2] , [3] , [4] , [5] , [19] , [20] , [21] , [22] , [23] . Furthermore, we used authentic viruses in neutralization assay whereas others did not.…”
Section: Discussionmentioning
confidence: 99%
“…The neo-coronavirus particle consists of an RNA gene chain, four structural proteins (spike (S) protein, small envelope (E) glycoprotein and membrane (M) glycoprotein, nucleocapsid (N) protein) and several auxiliary open reading frame (ORF) proteins. Among them is the S protein [ 88 , 89 , 90 , 91 , 92 , 93 ], which binds to angiotensin-converting enzyme 2 on the surface of human cells and is involved in the fusion and replication of viral and human cells; and the N protein [ 91 , 93 , 94 ], which is relatively conserved and against which the body can produce high levels of antibodies early in infection. These have both become major foci in the development of diagnostic epitopes for new coronaviruses.…”
Section: Applications In Diagnosismentioning
confidence: 99%